Sociology : Australian connections - Jureidini, Ray; Poole, Marilyn; Kenny, Sue (St. Leonards, N.S.W : Allen and Unwin, 2000)
The idea of society. The experiences of society.
Keywords: Sociology; Sociology; Sociology -- Australia